A new duplication in the mitochondrially encoded tRNA proline gene in a patient with dilated cardiomyopathy. (February 2013) - Cardena, Mari Maki Siria Godoy; Mansur, Alfredo José; Pereira, Alexandre Da Costa; Fridman, Cintia
<x xml:space="preserve">Abstract</x> Mitochondria provide an environment conducive to mutations in DNA molecules (mtDNA). Analyses of mtDNA have shown mutations potentially leading to many cardiovascular traits. Here, we describe a patient with dilated cardiomyopathy and new mtDNA duplication. The patient presented symptoms of heart failure New York Heart Association functional class III and was diagnosed with non-familial dilated cardiomyopathy with important left ventricular systolic dysfunction. Sequencing of mtDNA control region was done, and a 15 bp duplication was observed between nucleotides 16, 018 and 16, 032. Part of this duplication is localized within the tRNA proline gene (tRNAPro) that has an important role in cell protection against oxidative stress and is considered an important regulatory factor for cellular reactive oxygen species balance. This duplication could alter the stability or secondary structure of tRNAPro, affecting mt-protein synthesis. In turn, the presence of duplication in tRNAPro could cause some oxidative stress imbalance and, so, mitochondrial dysfunction could result in the pathogenicity.